Real interpolation method for transfer function approximation of distributed parameter system - Phu Tran Tin; Minh Tran; Le Anh Vu; Nguyen Quang Dung; Tran Thanh Trang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Distributed parameter system (DPS) presents one of the most complex systems in the control theory. The transfer function of a DPS possibly contents: rational, nonlinear and irrational components. This thing leads that studies of the transfer function of a DPS are difficult in the time domain and frequency domain. In this paper, a systematic approach is proposed for linearizing DPS. This approach is based on the real interpolation method (RIM) to approximate the transfer function of DPS by rational-order transfer function. The results of the numerical examples show that the method is simple, computationally efficient, and flexible.